Hashtag jurisprudence : terror and legality on Twitter - Sharp, Cassandra (Edward Elgar Publishing, 2022)
This thoroughly engaging book uses empirical analysis to illustrate that the response of individuals to global terror events, via social media, provokes an opportunity to interpret the ways in which individuals view their place in the world and their relation to law and justice. It is through analysing these responses that Cassandra Sharp demonstrates that a 'hashtag jurisprudence' can be constructed. Sharp offers a theory of law that combines narratives, the experience of terror and the expression of emotion through social media engagement. Using thought-provoking case studies of terrorist attacks between 2014 and 2018 from around the world, the book examines how social media has quickly become the new forum for members of the public to express their opinions on current law and justice. It further demonstrates the significant impact that comments on social media platforms can have on social justice issues and activism. This timely book will be required reading for academics in law, social sciences and humanities. Scholars with an interest in legal theory, philosophy, and law and emotion will find the case study findings insightful and informative.